2013
DOI: 10.1016/j.ctrv.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Developing a theoretical framework to illustrate associations among patient satisfaction, body image and quality of life for women undergoing breast reconstruction

Abstract: Within the field of breast reconstruction there is increasing focus on patient-reported outcomes related to satisfaction, body image, and quality of life. These outcomes are deemed highly relevant because the primary goal of breast reconstruction is to recreate the appearance of a breast (or breasts) that is satisfying to the patient. Prominent researchers have suggested the need to develop improved standards for outcome evaluation which can ultimately benefit patients as well as physicians. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 102 publications
4
61
0
Order By: Relevance
“…A smaller study representing 30 breast reconstruction patients demonstrated postoperative average of 64 (18) for satisfaction with the appearance of the reconstructed breast. 16 Our mean score for satisfaction with appearance of the breast was 61 (24), similar to the finding in these studies. In evaluating specific subtypes of reconstruction, a mean satisfaction score was reported as 65 (10.67) was reported 17 for 55 patients who underwent autologous reconstruction with DIEP and MS Free Tram Flaps.…”
Section: Discussionsupporting
confidence: 87%
“…A smaller study representing 30 breast reconstruction patients demonstrated postoperative average of 64 (18) for satisfaction with the appearance of the reconstructed breast. 16 Our mean score for satisfaction with appearance of the breast was 61 (24), similar to the finding in these studies. In evaluating specific subtypes of reconstruction, a mean satisfaction score was reported as 65 (10.67) was reported 17 for 55 patients who underwent autologous reconstruction with DIEP and MS Free Tram Flaps.…”
Section: Discussionsupporting
confidence: 87%
“…The number and percentage of patients that provided each survey response (1)(2)(3)(4)(5) were calculated for all questions. As appropriate, the Fischer exact and χ 2 tests were used to determine the association between each clinical variable of interest and survey responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of breast reconstruction (BR), the results of these studies are crucial because the primary goal of surgery is to reconstruct breasts that are pleasing to the patient. 2 Quality is also one of the major healthcare outcome measures that is going to be used in the future, and appropriate documentation in the area of BR is crucial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 The theoretical framework developed by Fingeret et al (2013) is specific to body image in women with breast cancer undergoing reconstruction and includes facets of perception, cognition, behavior, and emotion, as they relate to the function of the body after diagnosis and treatment for breast cancer. 6 …”
Section: Introductionmentioning
confidence: 99%